Dried corn germ in natural finishing programs reduces incidence of liver abscess - J.O. Wallace; James S. Drouillard; Christopher D. Reinhardt (Kansas Agricultural Experiment Station Research Reports, 2009)
Changes in consumer preference for beef produced without growth promotants, ionophores, or antibiotics and consumers' willingness to pay price premiums for such products have led some producers to begin raising beef under "natural" feeding regimens. Some natural programs prohibit use of injectable antibiotics, feed additive drugs, or growth promoting implants throughout the life of the animal. This creates challenges for maintaining efficient growth and preventing disease or metabolic disorders. A key problem facing producers who feed cattle under a natural regimen, without use of antibiotics such as tylosin and ionophores, is ruminal acidosis, which is commonly linked with liver abscesses. Abscesses are the primary cause for condemnation of livers, and severe abscesses have been shown to decrease daily gains (ADG) and efficiency of gain (F:G). In addition, severely abscessed livers can lead to greater carcass trim, ultimately reducing hot carcass weight (HCW) and dressing percentages. Fusobacterium necrophrum and Actinomyces pyogenes, normal inhabitants of the bovine rumen, are believed to be the primary and secondary bacteria that cause liver abscesses. Acidosis frequently causes ruminitis, which allows these bacteria to enter the portal circulation and migrate to the liver. The bacteria then colonize in the liver, ultimately creating abscesses. We previously observed a decrease in number of abscessed livers of approximately 5 to 7%, compared with controls, when dried, full-fat corn germ (GERM) was included in diets of finishing steers and heifers at rates ranging from 5 to 15%. These diets also included tylosin, which is commonly used to control liver abscesses. We speculated that adding GERM to the diet may decrease starch or alter intake patterns, resulting in decreased bouts of acidosis and subsequent ruminitis, or may suppress growth of F. necrophorum. Both scenarios could lead to decreased liver abscesses. The latter hypothesis was refuted in a previous study when we observed a tendency for increased concentrations of F. necrophorum when feeding supplemental fat at a rate of 4%. Objectives of this experiment were to assess the effect of GERM on growth performance, carcass yield and quality grades, and incidence of liver abscesses when fed to finishing cattle as part of a natural feeding regimen applied under commercial feeding conditions.
Keywords: Cattlemen& #x27; s Day; 2009; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1010; Kansas Agricultural Experiment Station contribution; no. 09-168-S; Beef; Cattle; Natural regiments; Germ